2017
DOI: 10.4238/gmr16018942
|View full text |Cite
|
Sign up to set email alerts
|

Identification and cloning of GOLDEN2-LIKE1 (GLK1), a transcription factor associated with chloroplast development in Brassica napus L.

Abstract: ABSTRACT. Photosynthesis is the process by which dry matter accumulates, which affects rapeseed yield. In this study, we identified GOLDEN2-LIKE1 (GLK1), located on chromosome A07 and 59.2 kb away from the single nucleotide polymorphism marker SNP16353A07, which encodes a transcription factor associated with the rate of photosynthesis in leaves. We then identified 96 GLK1 family members from 53 species using a hidden Markov model (HMM) search and found 24 of these genes, which were derived from 17 Brassicaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several genes affecting chloroplast development have been reported, and their role in leaf etiolation has been identified through studies of leaf mutants in Arabidopsis thaliana [ 18 ], rice [ 19 ], and tomato [ 20 ]. Golden 2-like ( GLK ) gene family includes GLK1 and GLK2 , which serve as regulation factors adjusting chloroplast development in various plant species, such as Brassica napus [ 21 ], tomato [ 22 , 23 ], wheat [ 24 ] and tobacco [ 25 ]. Recently, research on GLKs has rapidly increased and shown that GLKs control chloroplast development in green and non-green tissues [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several genes affecting chloroplast development have been reported, and their role in leaf etiolation has been identified through studies of leaf mutants in Arabidopsis thaliana [ 18 ], rice [ 19 ], and tomato [ 20 ]. Golden 2-like ( GLK ) gene family includes GLK1 and GLK2 , which serve as regulation factors adjusting chloroplast development in various plant species, such as Brassica napus [ 21 ], tomato [ 22 , 23 ], wheat [ 24 ] and tobacco [ 25 ]. Recently, research on GLKs has rapidly increased and shown that GLKs control chloroplast development in green and non-green tissues [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…When we think about improving photosynthesis, we tend to focus on foliar photosynthesis; however, green non‐foliar tissues can also perform photosynthesis in higher plants (Lawson & Milliken, 2023). Recent work is uncovering the role of GLKs in the greening of seed‐related organs, such as pods in Brassicaceae, hulls in barley, spikelets in rice, ears and awns of wheat and fruits in Solanaceae (Table 1) (Brand et al, 2014; Chen et al, 2018; Lupi et al, 2019; Nguyen et al, 2014; Pan et al, 2017; Powell et al, 2012; Taketa et al, 2021; Zheng et al, 2022). The importance, potential and influence of GLKs and chloroplast development for fruit breeders were revealed by the identification of a truncated version of SlGLK2 as the cause of the uniform ripening phenotype (Powell et al, 2012).…”
Section: Beyond Leaf Photosynthesismentioning
confidence: 99%
“…Similar findings have been reported in pepper, where CaGLK2 is important for natural variation in colour and, for peach, with only a single GLK (PpGLK1) that regulates leaf and immature fruit chlorophyll and chloroplast development (Brand et al, 2014; Chen et al, 2018). Siliques are another type of fruit that undergo a photosynthetic phase and research in Arabidopsis and B. napus have reported a role for GLKs in pod wall photosynthesis that contribute to seed yield traits such as seed weight and oil content (Fitter et al, 2002; Pan et al, 2017; Zhu et al, 2018).…”
Section: Beyond Leaf Photosynthesismentioning
confidence: 99%
“…Overexpression of GLK1 and GLK2 induces enhanced expression of chlorophyll related genes, with ectopic chlorophyll accumulation in non-photosynthetic organs [17,21,24]. As a transcription activator of photosynthesis-related genes [10,24,45,[70][71][72][73], an increasing transcript level was recorded in developing pericarp and embryo. The maximum transcript level was observed at 50 DAP in pericarp, while embryo showed the highest expression level at 20 DAP.…”
Section: Ahglk1b May Be Involved In Embryo Developmentmentioning
confidence: 99%